(untitled) (The Batuk, 2020)
Domestic violence has been a perennial experience among the women especially in developing countries. This includes both physical attack and coercive behavior which give rise to physical, sexual, and psychological impacts including depression, emotional distress, eating and sleeping disturbance, and physical symptoms, such as headaches and stomach aches. The present paper tries to explore the level of domestic abuses experienced by the married women Konjyosom Rural Municipality of Lalitpur. This study was based on exploratory and descriptive research design which is carried out in a Rural Municipality of Lalitpur district. This paper was conducted to examine the level of domestic violence and abuse which a married woman had to go through with their experience. This study reports that the married women are subject to domestic abuses of different kinds regardless of the ages, background, caste/ethnicity, religion, education level, occupation, and class.